Quand un pluriel cache un singulier : le cas de they - Jean ALBRESPIT (E-REA)
This paper examines the status of they-anaphora and the construction of anaphoric reference when the antecedent has the morphology of a singular noun (type: After a doctor graduates from medical school, they must take a licensing exam). Its aim is to account for the parameters which make it possible to transgress the syntactic constraints of number agreement. They anaphorises an antecedent with a generic – and most of the time an epicene – value. As English does not have an epicene pronoun, the pronoun selected has the advantage of including both genders but the disadvantage of transferring referential values towards genericity. The choice of this pronoun is not only dependent on a linguistic pattern but also on sociological and stylistic criteria. There are strategies to avoid the use of they – but they are unsatisfactory or else they modify the construction of reference.